Pengaruh Pengawasan Keuangan, Pemanfaatan TI, Komitmen Organisasi, Dan Kompetensi SDM Terhadap Keterandalan Pelaporan Keuangan Pemerintah Daerah Kabupaten Jember - Lelly Rahayu; Dessy Putri Andini (Jurnal Akuntansi Terapan dan Bisnis, 2021)
This study aims to determine the Effect of Financial Supervision, Utilization of IT, Organizational Commitment, and Competency of Human Resources on the Reliability of Financial Reporting for the Regional Government of Jember Regency. The study used a descriptive method with a quantitative approach, which was carried out by distributing research questionnaires to 100 employees of SKPD financial management in Jember Regency. The data analysis technique in this study used Structural Equation Modeling based on Partial Least Square (PLS-SEM). The results of this study are financial supervision, and organizational commitment have a significant positive effect on the reliability of the financial reporting of the Jember Regency Government. Meanwhile, the use of information technology (IT) and human resource competence has no effect.